THE REFORM OF PERSONAL INCOME TAXATION IN UKRAINE - E. Nosova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2016)
The changes that were made to the taxation of income of individuals are considered; impact of changes in taxation on the salary to be paid is calculated; has been demonstrated that the personal income taxation in Ukraine has progressive-regressive character; It revealed that the burden on a single hryvnia to pay was dropped; the validity of the application of the tax social benefits is examined; has been revealed that the application of a tax social benefits leads to discrimination against individuals whose income slightly exceeds the cutoff amount for the use of tax incentives; the tax burden on wages and its dynamics are analyzed; enterprise savings by reducing the rate of the single social contribution are defined; the possible increase in wages while maintaining enterprise-level costs is calculated.